Multimodality, meaning, and institutions - Hollerer, Markus A., active 2017; Daudigeos, Thibault; Jancsary, Dennis (Research in the sociology of organizations, 2017)
The insight that institutions, and the communicative practices that create, sustain, and challenge them, are multimodal accomplishments has garnered increasing attention from scholars in organization and management research over the last decade. Traditional understanding of social knowledge and meaning as being constituted primarily through verbal discourse has been challenged and extended by work that has promoted the centrality of visual, material, and other sign systems (e.g., audio, gestures, layout) for constructing social reality. While some discursive approaches to organizations and institutions have acknowledged the existence and relevance of modes other than the verbal for some time, systematic research on multimodality has remained rather sparse. In particular, the interaction and orchestration of multiple modes remains terra incognita with considerable empirical, methodological, and theoretical stakes. Together, 54A and 54B of Research in the Sociology of Organizations investigate these issues with innovative research that focuses on the relationship between different modes in the emergence, diffusion, maintenance, and challenge of social meanings and institutions. Individual contributions demonstrate the potential of multimodal approaches to rejuvenate and extend the study of institutions, they revisit research on classic phenomena in organization theory through a multimodal lens, and advance the design of relevant and rigorous methods of analysis for the study of multimodal communicative practices.